PERAN SPIRITUALITAS DAN RELIGIUSITAS BAGI GURU DALAM LEMBAGA PENDIDIKAN - Arwani, Agus (Forum Tarbiyah, 2013)
Teachers are human figures that occupy the position and play an important role in education. Religiosity is the depth of a person's religious appreciation and belief in the existence of God is realized by obeying commands and prohibitions with kaiklasan away with a whole heart and soul and body. Spirituality avoids the formal and ceremonial connotations of religion; it is non denominational, non-hierarchical, and nonecclesiastical. Spirituality implies an inner search for meaning or fulfillment that may be undertaken by anyone regardless of religion. Religiosity and spirituality religious in works that are expected to contribute constructively to build a work environment and the image of the teachers profession (teachers refer not just limited to educate, but also all those who have a background in teaching education and cultivate a job in the field education for more professional, high integrity and  accountable.